(2) 3y - 3x = -6

**y = 0**

**x=2**

I have done this problem several times. and can not seem to get the correct work and check.

Tutors, sign in to answer this question.

(1) 4y + 2x = 4

(2) 3y - 3x = -6

(2) 3y - 3x = -6

Let's solve equation (1) for x:

4y + 2x = 4

2x = 4 - 4y

x = 2 - 2y

Now let's substitute 2-2y in place of x in equation 2:

3y - 3x = -6 [Equation (2)]

3y - 3(2-2y) = -6 [Substituted 2-2y for x]

3y - 6 + 6y = -6

9y = 0

Find x:

x = 2 - 2y

x = 2 - 2(0)

Check:

4y+2x = 4

4(0)+2(2) = 4

4 = 4

3y-3x=-6

3(0)-3(2) = -6

-6 = -6

Hi Adena,

4y+2x=4......eq 1

3y-3x=-6.......eq 2

Divide eq 2 by 3, we get,

y-x=-2

adding x on both the sides,

y=x-2..........eq 3

substituting value of y in eq 1, we get,

4(x-2)+2x=4

4x-8+2x=4

6x=12

x=2

substituting value of x in eq 3, we get,

y=2-2

y=0

Check: LHS of eq 1=4y+2x=4(0)+2(2)= 4=RHS

LHS of eq 2= 3y-3x=3*0-3*2=-6 = RHS

Ans: { x=2,y=0}

Meena from Strongsville,OH

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.